Regularities of Misorientation in [111] FCC Single Crystals; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Lychagin D. V. Dmitry Vasilievich (2017, 2017)
Title screen